The attention and action. Experimental study of the doctor test Valdizán - Bustamante Ruíz, Carlos E. (1937)
Attention can be defined as "the whole effort of the spirit that limiting a particular region in the field of consciousness, vividly illuminates the contents of that field and keeps well, distinct and clear, as he contemplates or study."